Konsumsi Jus Wortel Selama Kemoterapi Meningkatkan Kadar Hemoglobin Pasien Kanker Serviks Stadium II-B - Ni Ketut Alit Armini; Sri Yuniarti; Alvarea Enggusti (Jurnal Ners, 2007)
Introduction: Ca Cervix patients who had a chemotherapy may experience depletion of Hb level. Hb level can increase by giving a natural carrot juice.  The nutritional  content of carrot juice such as beta karoten, ferrum, calcium, vitamin B, vitamin C and protein can assist bone marrow produce Hb and lymphosite. The objective of this study was to analyze the effect of carrot juice consumption during chemotherapy on Hb level of patients with Ca Cervix stage II-b. Method: This study used a quasy experimental design and the population was the patients who stayed at gynecology room. The sampling technique was used consecutive sampling, with the total sample were 16 respondents. Data were collected by taken the blood sample and analyzed by using Paired t-Test and Independent t-Test. Result: The result showed that carrot juice influent on the change of rate of Hb with significance level (p=0.005). Discussion: It can be concluded that by giving carrot juice to the patients with experiencing chemotherapy, can increase Hb level. Further studies are recommended to analyze the effect of carrot Juice on patient with low Hb level during Chemotherapy for further possibilities.